Culture Of Postpartum Care In Indonesia - Qoyimah, Ilmiatus; Anggorowati, Anggorowati; Dwidiyanti, Meidiana (Universitas Islam Lamongan, 2022)
The puerperium or postpartum period is defined as the period that begins after the expulsion of the placenta after the birth of the baby and ends when the reproductive organs return to their pre-pregnancy state and lasts for 40 days. During the postpartum period, there are various kinds of care that mothers get, one of which is culture-based care which can affect the care process. The purpose of this Literature Review is to obtain a theoretical basis that can support solving the problem being studied. The preparation of this article was carried out using the Literature Review method by conducting a search based on the keywords